Haemoadsorption reduces the inflammatory response and improves blood flow during ex vivo renal perfusion in an experimental model - Hosgood, Sarah A. (J Transl Med, 2017)
BACKGROUND: Ex-vivo normothermic perfusion strategies are a promising new instrument in organ transplantation. The perfusion conditions are designed to be protective however the artificial environment can induce a local inflammatory response. The aim of this study was to determine the effect of incorporating a Cytosorb adsorber into an isolated kidney perfusion system. METHODS: Porcine kidneys were subjected to 22 h of cold ischaemia then reperfused for 6 h on an ex vivo reperfusion circuit. Pairs of kidneys were randomised to either control (n = 5) or reperfusion with a Cytosorb adsorber (n = 5) integrated into the circuit. Tissue, blood and urine samples were taken for the measurement of inflammation and renal function. RESULTS: Baseline levels of cytokines (IL-6, TNFα, IL-8, IL-10, IL-1β, IL-1α) were similar between groups. Levels of IL-6 and IL-8 in the perfusate significantly increased during reperfusion in the control group but not in the Cytosorb group (P = 0.023, 0.049). Levels of the other cytokines were numerically lower in the Cytosorb group; however, this did not reach statistical significance. The mean renal blood flow (RBF) was significantly higher in the Cytosorb group (162 ± 53 vs. 120 ± 35 mL/min/100 g; P = 0.022). Perfusate levels of prostaglandin E2 were significantly lower in the Cytosorb group (642 ± 762 vs. 3258 ± 980 pg/mL; P = 0.0001). Levels of prostacyclin were significantly lower in the Cytosorb group at 1, 3 and 6 h of reperfusion (P = 0.008, 0.003, 0.0002). Levels of thromboxane were also significantly lower in the Cytosorb group throughout reperfusion (P = 0.005). Haemoadsorption had no effect on creatinine clearance (P = 0.109). CONCLUSION: Haemoadsorption can reduce the inflammatory response and improve renal blood flow during perfusion. Nonetheless, in this model haemoadsorption had no influence on renal function and this may relate to the broad-spectrum action of the Cytosorb adsorber that also removes potentially important anti-inflammatory mediators.